2019
DOI: 10.3897/zookeys.814.28869
|View full text |Cite
|
Sign up to set email alerts
|

New species of bone-eating worm Osedax from the abyssal South Atlantic Ocean (Annelida, Siboglinidae)

Abstract: A new species of bone-eating annelid, Osedaxbraziliensissp. n., found in a sunken whale carcass at a depth of 4,204 m at the base of the São Paulo Ridge in the South Atlantic Ocean off the Brazilian coast is described. The organism was retrieved using the human-occupied vehicle Shinkai 6500 during the QUELLE 2013 expedition. This is the 26th species of the genus and the first discovery from the South Atlantic Ocean, representing the deepest record of Osedax worldwide to date. This species morphologically resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…mucofloris ) and off Brazil ( O . braziliensis ) [61], but these are phylogenetically quite distant in belonging to Osedax clade IV [54].…”
Section: Discussionmentioning
confidence: 99%
“…mucofloris ) and off Brazil ( O . braziliensis ) [61], but these are phylogenetically quite distant in belonging to Osedax clade IV [54].…”
Section: Discussionmentioning
confidence: 99%
“…The death and fall of large marine mammals can bring temporary and successional oases within such environments, as macrofaunal communities compete to exploit these large influxes of organic matter (Smith and Baco 2003). One such specialist, Osedax (Annelida, Siboglinidae) (Goffredi et al 2004;Rouse et al 2004) have successfully colonised these unusual habitats, feeding and living within vertebrate bones from shallow and deep waters of the Pacific, Atlantic and Antarctic Oceans, and even the Mediterranean Sea (see Fujiwara et al 2019). Commonly known as the 'bone-eating' worms, free-swimming Osedax larvae settle upon vertebrate carcasses and develop a distinct network of vascularised 'roots' which proliferate into the bone (Goffredi et al 2005(Goffredi et al , 2007Miyamoto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms by which endosymbionts acquire such nutrients remain to be fully understood (Goffredi et al 2014). We now know of 26 Osedax species (Rouse et al 2004(Rouse et al , 2008(Rouse et al , 2015Glover et al 2005Glover et al , 2013Fujikura et al 2006;Braby et al 2007;Fujiwara et al 2007;Goffredi et al 2007;Vrijenhoek et al 2008Vrijenhoek et al , 2009Amon et al 2014;Taboada et al 2015;Sumida et al 2016), of which 15 were formally described within the last few years (Rouse et al 2018;Fujiwara et al 2019), and a few, as yet remain undescribed, demonstrating the increased knowledge of Osedax prevalence and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Although Osedax was first described only 15 years ago (Rouse et al, 2004), there are already 26 described species and an additional 9 unnamed OTUs (Rouse et al, 2018;Fujiwara et al, 2019). The Monterey Bay in California, from where the first Osedax species was described, has the highest documented diversity with 18 named species (Rouse et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The only described species of Osedax in the North Atlantic, Osedax mucofloris, was originally described from 125 m depth in a fjord on the west coast of Sweden (Glover et al, 2005), and has subsequently been reported from a similar depth on the west coast of Norway (Schander et al, 2010) and from 1000 m depth in the Setubal Canyon, off Portugal (Hilario et al, 2015). One new species of Osedax and four OTUs were recently recorded from the deep southwest Atlantic (4204 m depth off Brazil; Fujiwara et al, 2019;Shimabukuro and Sumida, 2019). In addition, there are two undescribed putative species: one from the Setubal Canyon off Portugal (1000 m depth; Hilario et al, 2015) and one from the Mediterranean (53 m depth; Taboada et al, 2015).…”
Section: Introductionmentioning
confidence: 99%